Development and Function of the Ovary and the Uterus in Goats - Mathai E (Department of Physiology, College of Veterinary and Animal Sciences, 1984)
In Alpine-Malabari cross-bred female kids., the birth weight was found to be 1.88-+0.048 kg. The gain in weight was maximum (15.36%)during the first 30 days but was only marginal after 210 days. Linear measurements of teat also showed changes parallel to the body weight. From 30th day onwards, many small follicies were seen projecting from the ovarian surface. Appearance of large follicles on 150th day indicated the attainment of full functional activity of the ovary by that time. The right ovary weighed significantly more than that of the left. The weights of thyroid, adrenals and pituitary, as percentage to weight at slaughter, showed a linear reduction as the age advanced. Onset of puberty was observed to occur at 231.40_+6.271 days in Alpine-Malabari goats. The weight at puberty was 13.19_+0.35 kg. The length of oestrous cycle was 508.17_+ 66.55 hours (12.17 days). The occurence of short (5-15 days), medium (16.24 days) and long (25 days and above) oestrous cycles were recorded as 6.32 per cent, 84.09 per cent and 9.09 per cent respectively. The average duration of oestrum was 49.43 _+ 6.18 hours. The weight of ovary was maximum on the 18th day of oestrum cycle in adult Alpine-Malabari cross-bred goats. The weight of fallopian tube was highest on the day of oestrum. Packed cell volume and total leukocyte count were significantly more on the day of oestrum. In the differential distribution of leuckocyts, Iymphocytes registered a low count while the number of neutrophils and eosinophils recorded a rise on the day of estrum suggestive of a stress-like state. At brith, the ovary showed a single layer of cuboidal cells in the germinal epithelium. Primary, secondary and degenerating follicles were seen. On 30th day, tertiary follicles also were noted. Large ovulatory follicles were seen on the 120th day in histological studies. Uterine mucosa colummar epithelium. at brith was lined by tall pseudostratified Uterine lumen was almost obiterated by endometrial folds. Five different layers viz. epithellal lining, vascular layer, stratum compactum, stratum spongiosum and stratum basale could be distinguished from 30th day. Active secretion of endometrial glands was noted by 150 days. Intense alkaline phosphate (ALP) activity was noted in theca cells of follicles and in luteal cells. Acid cells of endometrium and glands showed high activities of alkaline and acid phosphatases. During luteal phase of oestrous cycle both ACP and ALP activities were more than those in follicular phase. The serum glutamate oraloacetate transaminase (GOT) and glutamate pyruvate transaminase (GPT) levels were more corresponding to the period of higher growth rate. On the day of oestrum GOT values in serum, ovarian and uterine tissue were significantly more. However, GPT, ALP and ACP activities did not reveal any significant difference during the four phases of oestrous cycle. Administration of gonadotropin relasing hormone (GnRH) resulted in an increase in weight gain of kids. In the treated kids early onset of puberty and a higher number of ovarian follicles were observed. Growth of ovarian tissue and tubular genitalia- especially the uterus- were more in treated kids.